PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) BERBATU MEDIA FLIPBOOK TERHADAP KEMAMPUAN BERPIKIR KRITIS PPKn PESERTA DIDIK KELAS IV SDN 2 METRO SELATAN - Anjela, Anggun; Astuti, Nelly; Rohman, Fathkhur (Elementeris : Jurnal Ilmiah Pendidikan Dasar Islam, 2024)
The problem in this study is the low critical thinking skills of fourth grade students at SD Negeri 2 Metro Selatan. The purpose of this study was to determine the effect of the contextual teaching and learning (CTL) model assisted by flipbook media on students' critical thinking skills. Quasi Experimental Group Design is the research methodology used here. 46 persons made up the study's sample, which was chosen using the saturated sample type non-probability sampling technique. gathering data through observation, documenting, and testing methods. A straightforward linear regression test was used to test the hypothesis, and the results showed that Fcount ≥ Ftable (22.26>4.32), indicating that Ha was accepted and Ho was rejected. The study's findings demonstrated that, during the 2023–2024 academic year, PPKn students in class IV SD Negeri 2 Metro Selatan's critical thinking abilities were impacted by the Contextual Teaching and Learning (CTL) model with the help of flipbook media. Keywords: Critical thinking skills, Contextual Teaching and Learning (CTL), Flipbook.